HSPA9 reduction exacerbates symptoms and cell death in DSS-Induced inflammatory colitis - Soyoung Jang; Soyeon Jang; Jiwon Ko; Ji-Eun Bae; Hyejin Hyung; Ji Yeong Park; Su-Geun Lim; Sijun Park; Song Park; Junkoo Yi; Seonggon Kim; Myoung Ok Kim; et al. (Scientific Reports, 2024)
Abstract Inflammatory bowel disease (IBD) is a chronic inflammatory condition that is influenced by various factors, including environmental factors, immune responses, and genetic elements. Among the factors that influence IBD progression, macrophages play a significant role in generating inflammatory mediators, and an increase in the number of activated macrophages contributes to cellular damage, thereby exacerbating the overall inflammatory conditions. HSPA9, a member of the heat shock protein 70 family, plays a crucial role in regulating mitochondrial processes and responding to oxidative stress. HSPA9 deficiency disrupts mitochondrial dynamics, increasing mitochondrial fission and the production of reactive oxygen species. Based on the known functions of HSPA9, we considered the possibility that HSPA9 reduction may contribute to the exacerbation of colitis and investigated its relevance. In a dextran sodium sulfate-induced colitis mouse model, the downregulated HSPA9 exacerbates colitis symptoms, including increased immune cell infiltration, elevated proinflammatory cytokines, decreased tight junctions, and altered macrophage polarization. Moreover, along with the increased mitochondrial fission, we found that the reduction in HSPA9 significantly affected the superoxide dismutase 1 levels and contributed to cellular death. These findings enhance our understanding of the intricate mechanisms underlying colitis and contribute to the development of novel therapeutic approaches for this challenging condition.